Effect of Postharvest handling on Quality Attributes of Passion Fruits (Passiflora edulis Sims var.) - Lagat, Cyrus K.; Omami, E. N; Mutui , T. M; Rop , N. K. (African Journal of Education,Science and Technology (AJEST), 2018)
In Kenya, Passion fruit is becoming part of solution in staving- off hunger and malnourishment. Most of the underutilized fruits passion fruits included are often among those which have the greatest potential in terms of nutrition and income generation for small holders. Passion fruit is underutilized because of the significant amounts that go into waste during peak production. The objective of this study was to evaluate the effect of postharvest handling on quality of passion fruit (Passiflora edulis sims var) in Uasin -gishu county. Four hundred and eighty (480) passion fruits were harvested from farmer’s fields in Soy and Kapseret sub-counties in Uasin Gishu County and postharvest treatments applied, this included harvesting at two color maturity stages (at 75% and 25% colouring), detachment of the fruit with a 5 cm stalk attached and others with no stalk attached, storage of fruit under ambient conditions and others in polythene sheets. Treated fruits were then taken to Chemelil Sugar Company Laboratory where they were stored and analyzed periodically for 28 days. The experiment was laid out in a completely randomized design (CRD) with three replicates. Passion fruits were analyzed for Weight change during storage, Total Titratable Acidity (TTA), Total Soluble Solids (TSS) and Pulp weight. The data collected was subjected to Analysis of Variance (ANOVA) using GenStat version 14th edition. The color at which passion fruit was harvested greatly affected its titratable acidity, pulp weight and its brix. In addition the mode of storage significantly impacted the fruit total titratable acidity, pulp weight and whole fruit weight. On the other hand the point at which the fruit was detached from the mother plant did not significantly affect the measured quality attributes other than total titratable acidity. Storage interval significantly affected the measured quality attributes of passion fruit The key aspects that the farmers in Uasin Gishu County should observe when harvesting the produce include; harvest the produce at 75% color maturity stage as well as employ the use of recommended modified atmosphere packaging material as this will greatly impact the fruits chemical and organoleptic quality attributes thus influencing its shelf life.